Heterogeneous copper alloy current collector and preparation method and application thereof
By adopting a heterogeneous copper alloy structure in the current collector of lithium-ion batteries, combining nano-copper alloy and micro-crystalline copper layer, the problem of poor binding force between the composite current collector layers is solved, significantly improving the conductivity, strength and plasticity of the current collector, and improving the performance and life of the lithium-ion battery.
Patent Information
- Application Number
- CN202510004534.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-02
AI Technical Summary
The existing composite liquid collectors have poor interlayer bonding forces, resulting in insufficient conductivity and strong plasticity, affecting the performance and life of lithium-ion batteries.
Heterogeneous copper alloy current collector is used, including a nano-copper alloy layer and a micro-crystalline copper layer. The micro-crystalline copper layer is arranged between adjacent nano-copper alloy layers. Through the mutual cooperation between the soft and hard layers, the strength, conductivity and inter-layer bonding force of the current collector are enhanced.
It achieves high strength, high plasticity and high conductivity, improves the overall performance of the current collector, solves the problem of poor bonding between layers, and simplifies the preparation process, which is suitable for large-scale production.
Smart Images

Figure CN119812353A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion secondary batteries, and in particular relates to a heterogeneous copper alloy current collector and a preparation method and application thereof. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] As the current mainstream portable energy storage device, lithium-ion batteries have been widely used in electric vehicles, mobile communications, energy storage and other fields. The negative electrode current collector is one of the key components of lithium-ion batteries. Its main function is to carry the negative electrode active material and collect current. Traditional negative electrode current collectors are mainly made of copper foil, which has the problems of low strength and poor corrosion resistance, which to some extent limits the performance and life of lithium-ion batteries. In order to overcome these shortcomings, composite current collectors have emerged as a new type of current collector material in recent years, and have received widespread attention due to their excellent performance.
[0004] Composite current collectors usually adopt a sandwich structure, and the middle layer is often made of polymer materials, such as polyethylene, polypropylene, etc. These polymer materials have the advantages of low manufacturing cost, high safety, and high energy density. For example, patent CN 115763829A discloses a composite current collector that can enhance conductivity, with a polymer support layer as the central layer, and a nano silver wire enhanced conductive layer, a metal layer, and a graphene enhanced conductive layer are symmetrically arranged on both sides. For example, patent CN 116207270A discloses a composite current collector, wherein a masterbatch, a conductive agent, a coupling agent, and a filler are mixed and molded and stretched to obtain a polymer film layer, and the polymer film layer is roughened; the roughened polymer film layer is primed by magnetron sputtering; and the primed polymer film is plated with a metal layer to obtain a composite current collector.
[0005] The above-mentioned composite current collector can enhance the conductivity of the current collector or the bonding force between the polymer layer and the metal layer, but the bonding between the polymer layer and the outer metal layer is often a physical bonding with weak bonding force and high resistance, which may cause peeling between the outer metal layer and the polymer layer during the battery charging and discharging process, thereby affecting the performance and life of the battery. In addition, the preparation process of this composite current collector is relatively complicated, requiring multiple steps and complex equipment, which further limits its promotion in practical applications. Therefore, it is necessary to seek a new method for composite current collectors that can improve conductivity while ensuring interlayer bonding and improving strong plasticity. Summary of the invention
[0006] In order to solve the deficiencies of the prior art, the purpose of the present invention is to provide a heterogeneous copper alloy current collector and its preparation method and application. The heterogeneous copper alloy current collector provided by the present invention solves the problem of poor interlayer bonding of the composite current collector and improves the current collector conductivity and strong plasticity. In order to achieve the above purpose, the technical solution of the present invention is:
[0007] A first aspect of the present invention provides a heterogeneous copper alloy current collector, comprising a nano-copper alloy layer and a micron-crystalline copper layer, wherein the micron-crystalline copper layer is disposed between adjacent nano-copper alloy layers.
[0008] In the heterogeneous copper alloy current collector provided by the present invention, the outer layer is a hard layer, which is a high-strength nanocrystalline copper alloy, used to improve the strength and conductivity of the current collector. The middle layer is a soft layer, which is a micron-crystalline copper with high conductivity and high plasticity, and high strength, high plasticity and high conductivity are achieved through the cooperation between the soft and hard layers.
[0009] It should be noted that the terms micron crystal and nano crystal refer to grains of different sizes. Both nano crystal and micron crystal are a new type of crystalline material. The difference between them lies in the different grain sizes. The general classification standard is that grains smaller than 100nm are called nano crystals, and grains between 100nm and 1μm are called micro crystals.
[0010] In some embodiments of the present invention, the number of the micron-crystalline copper layer is 1-4.
[0011] In some embodiments of the present invention, the copper alloy includes one of a copper-silver alloy, a copper-tin alloy, a copper-nickel alloy and a copper-gold alloy.
[0012] Preferably, the content of impurity elements in the copper alloy is less than or equal to 10%.
[0013] In some embodiments of the present invention, the thickness of the heterogeneous copper alloy current collector is 6-16 μm, and the thickness ratio of the nano copper alloy layer to the micron crystalline copper layer is (1-3):(1-3).
[0014] A second aspect of the present invention provides a method for preparing the above-mentioned heterogeneous copper alloy current collector, comprising the following steps:
[0015] Copper alloy electroplating solution and micron-crystal copper electroplating solution are respectively prepared;
[0016] In the plating solution, a nano copper alloy layer and a micron crystalline copper layer are electrodeposited on a substrate according to a set structure;
[0017] The heterogeneous copper alloy current collector is obtained by peeling, washing and drying.
[0018] It should be noted that the peeling refers to peeling the heterogeneous copper alloy current collector deposited on the substrate from the substrate. The substrate can be a nickel plate. In order to ensure the purity of the nano copper alloy layer in the obtained heterogeneous copper alloy current collector, the nickel plate needs to be polished, cleaned, degreased and activated before use.
[0019] The heterogeneous copper alloy current collector obtained by stripping is cleaned and dried to remove the residual plating solution and impurities to ensure the purity and stability of the heterogeneous copper alloy current collector. During the stripping process, appropriate stripping agents and process conditions can be used to ensure that the integrity and performance of the heterogeneous copper alloy current collector are not affected.
[0020] In some embodiments of the present invention, the copper alloy electroplating solution contains a refiner, and the refiner includes one or more of gelatin, thiourea, 2-mercaptobenzimidazole and sodium poly(disulfide-bis(propylene sulfonate)).
[0021] Preferably, the concentration of the refiner in the copper alloy electroplating solution is 0.005-0.05 g / L.
[0022] In some embodiments of the present invention, the micron-crystalline copper electroplating solution is one of a sulfate system, a nitrate system, a pyrophosphate system and a citrate system.
[0023] In some embodiments of the present invention, the electrodeposition includes one of direct current electrodeposition and pulse electrodeposition.
[0024] Preferably, when the nano copper alloy layer is electrodeposited, the current density is 2-20 mA / cm 2 , the deposition time is 10-60min.
[0025] Preferably, when the micron-crystalline copper layer is electrodeposited, the current density is 20-50 mA / cm 2 , the deposition time is 5-30min.
[0026] It should be noted that the thickness ratio of the nano copper alloy layer to the micron crystalline copper can be controlled by controlling the deposition time and current density.
[0027] Preferably, the electrodeposition process is carried out in a protective gas atmosphere. Preferably, the protective gas includes one of nitrogen, argon and helium.
[0028] In some embodiments of the present invention, after the electrodeposition is completed to form a nano copper alloy layer or a micron crystalline copper layer, it is washed with water, acid washed and washed with water before the next deposition is carried out.
[0029] The third aspect of the present invention provides a negative electrode sheet, which includes the above-mentioned heterogeneous copper alloy current collector or the heterogeneous copper alloy current collector prepared by the above-mentioned preparation method and a mixed slurry layer containing negative electrode materials arranged on the surface of the heterogeneous copper alloy current collector.
[0030] A fourth aspect of the present invention provides a lithium ion battery, comprising the above-mentioned heterogeneous copper alloy current collector, the heterogeneous copper alloy current collector prepared by the above-mentioned preparation method, or the above-mentioned negative electrode sheet. The beneficial effects of the present invention are:
[0031] The present invention provides a heterogeneous copper alloy current collector, comprising a nano copper alloy layer and a micron-crystalline copper layer, wherein the micron-crystalline copper layer is arranged between adjacent nano copper alloy layers. The outer layer is a hard layer, which is a high-strength copper alloy, and is used to improve the strength and conductivity of the current collector. The middle layer is a soft layer, which is a micron-crystalline copper with high conductivity and high plasticity. High strength, high plasticity and high conductivity are achieved by mutual cooperation between the soft and hard layers. After testing, the peel strength of the heterogeneous copper alloy current collector provided by the present invention is above 420N / m, which solves the problem of poor interlayer bonding force in the existing composite current collector. The heterogeneous copper alloy current collector obtained by the embodiment of the present invention has excellent peel strength, indicating that it has excellent interlayer bonding force, and at the same time it has more excellent strength, ductility and good electrical conductivity, indicating that this heterogeneous structure can effectively improve the overall strength and plasticity of the current collector.
[0032] The preparation method of the heterogeneous copper alloy current collector provided by the present invention adopts a traditional electroplating process, and the process is simpler and is conducive to large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0034] Figure 1 This is a cross-sectional TEM image of the heterogeneous copper-silver alloy current collector obtained in Example 1 of the present invention. DETAILED DESCRIPTION
[0035] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.
[0036] Wherein, the reagents or raw materials used in the following examples are all commercially available or homemade.
[0037] It should be noted that in the following examples, "silver nitrate 40 mL / L 0.1 M" means that 40 mL of 0.1 M silver nitrate solution is added to every 1 L of solution A.
[0038] Example 1
[0039] A method for preparing a heterogeneous copper alloy current collector comprises the following steps:
[0040] 1. Prepare nano copper-silver alloy electroplating solution: solution A is obtained by mixing 150 g / L potassium iodide, 10 g / L potassium nitrate and 40 mL / L silver nitrate at 0.1 M. 500 g / L copper sulfate and 150 g / L potassium pyrophosphate are dissolved in deionized water at a constant temperature to obtain solution B. Solution A and solution B are mixed in equal proportions, and then 0.005 g / L thiourea is added.
[0041] 2. Prepare micron-crystalline copper electroplating solution: the plating solution formula is: copper sulfate 75g / L, sulfuric acid 180g / L.
[0042] 3. Deposition of nano copper-silver alloy layer: In the nano copper-silver alloy electroplating solution, a nano copper-silver alloy layer is deposited on the nickel plate that has been ground, polished, cleaned, degreased and activated using direct current deposition. The deposition current density is 10 mA / cm 2 , deposition time 20min, thickness 2μm.
[0043] 4. Deposit a micron-crystalline copper layer: In a micron-crystalline copper electroplating solution, deposit a micron-crystalline copper layer on the nano-copper-silver alloy layer obtained in step 3 at a current density of 20 mA / cm 2 , deposition time 10min, thickness 2μm.
[0044] 5. Depositing a nano copper-silver alloy layer: using the method of step 3, depositing a nano copper-silver alloy layer on the micron-crystalline copper layer obtained in step 4.
[0045] 6. After the deposition is completed, a heterogeneous copper-silver alloy current collector with a hard layer to soft layer ratio of 2:1, a thickness ratio of 1:1, and a total thickness of 6 μm is obtained by peeling off from the nickel plate substrate. The heterogeneous copper-silver alloy current collector obtained by peeling off is cleaned and dried.
[0046] Figure 1 This is a TEM image of the cross section of the heterogeneous copper-silver alloy current collector obtained in Example 1. It can be seen from the image that the upper layer of the heterogeneous copper-silver alloy current collector is nanocrystalline, the middle layer is micron-crystalline, and the grain size is 1.5-2.5μm.
[0047] Example 2
[0048] A method for preparing a heterogeneous copper alloy current collector comprises the following steps:
[0049] 1. Prepare nano copper-silver alloy electroplating solution: solution A is obtained by mixing 150 g / L potassium iodide, 10 g / L potassium nitrate and 40 mL / L silver nitrate at 0.1 M. 500 g / L copper sulfate and 150 g / L potassium pyrophosphate are dissolved in deionized water at a constant temperature to obtain solution B. Solution A and solution B are mixed in equal proportions, and then 0.005 g / L thiourea is added.
[0050] 2. Prepare micron-crystalline copper electroplating solution: the plating solution formula is: copper sulfate 75g / L, sulfuric acid 180g / L.
[0051] 3. Deposition of nano copper-silver alloy layer: In the nano copper-silver alloy electroplating solution, a nano copper-silver alloy layer is deposited on the nickel plate that has been ground, polished, cleaned, degreased and activated using direct current deposition. The deposition current density is 10 mA / cm 2 , deposition time 40min, thickness 4μm.
[0052] 4. Deposit a micron-crystalline copper layer: In a micron-crystalline copper electroplating solution, deposit a micron-crystalline copper layer on the nano-copper-silver alloy layer obtained in step 3 at a current density of 20 mA / cm 2 , deposition time 10min, thickness 2μm.
[0053] 5. Depositing a nano copper-silver alloy layer: using the method of step 3, depositing a nano copper-silver alloy layer on the micron-crystalline copper layer obtained in step 4.
[0054] 6. After the deposition is completed, a heterogeneous copper-silver alloy current collector with a hard layer to soft layer ratio of 2:1, a thickness ratio of 2:1, and a total thickness of 10 μm is obtained by peeling off from the nickel plate substrate, and the heterogeneous copper-silver alloy current collector obtained by peeling is cleaned and dried.
[0055] Example 3
[0056] A method for preparing a heterogeneous copper alloy current collector comprises the following steps:
[0057] 1. Prepare nano copper-silver alloy electroplating solution: solution A is obtained by mixing 150 g / L potassium iodide, 10 g / L potassium nitrate and 40 mL / L silver nitrate at 0.1 M. 500 g / L copper sulfate and 150 g / L potassium pyrophosphate are dissolved in deionized water at a constant temperature to obtain solution B. Solution A and solution B are mixed in equal proportions, and then 0.005 g / L thiourea is added.
[0058] 2. Prepare micron-crystalline copper electroplating solution: the plating solution formula is: copper sulfate 75g / L, sulfuric acid 180g / L.
[0059] 3. Deposition of nano copper-silver alloy layer: In the nano copper-silver alloy electroplating solution, a nano copper-silver alloy layer is deposited on the nickel plate that has been ground, polished, cleaned, degreased and activated using direct current deposition. The deposition current density is 10 mA / cm 2 , deposition time 30min, thickness 3μm.
[0060] 4. Deposit a micron-crystalline copper layer: In a micron-crystalline copper electroplating solution, deposit a micron-crystalline copper layer on the nano-copper-silver alloy layer obtained in step 3 at a current density of 20 mA / cm 2 , deposition time 5min, thickness 1μm.
[0061] 5. Depositing a nano copper-silver alloy layer: using the method of step 3, depositing a nano copper-silver alloy layer on the micron-crystalline copper layer obtained in step 4.
[0062] 6. After the deposition is completed, a heterogeneous copper-silver alloy current collector with a hard layer to soft layer ratio of 2:1, a thickness ratio of 3:1, and a total thickness of 7 μm is obtained by peeling off from the nickel plate substrate. The heterogeneous copper-silver alloy current collector obtained by peeling off is cleaned and dried.
[0063] Example 4
[0064] A method for preparing a heterogeneous copper alloy current collector comprises the following steps:
[0065] 1. Prepare nano copper-silver alloy electroplating solution: solution A is obtained by mixing 150 g / L potassium iodide, 10 g / L potassium nitrate and 40 mL / L silver nitrate at 0.1 M. 500 g / L copper sulfate and 150 g / L potassium pyrophosphate are dissolved in deionized water at a constant temperature to obtain solution B. Solution A and solution B are mixed in equal proportions, and then 0.005 g / L thiourea is added.
[0066] 2. Prepare micron-crystalline copper electroplating solution: the plating solution formula is: copper sulfate 75g / L, sulfuric acid 180g / L.
[0067] 3. Deposition of nano copper-silver alloy layer: In the nano copper-silver alloy electroplating solution, a nano copper-silver alloy layer is deposited on the nickel plate that has been ground, polished, cleaned, degreased and activated using direct current deposition. The deposition current density is 10 mA / cm 2 , deposition time 20min, thickness 2μm.
[0068] 4. Deposit a micron-crystalline copper layer: In a micron-crystalline copper electroplating solution, deposit a micron-crystalline copper layer on the nano-copper-silver alloy layer obtained in step 3 at a current density of 20 mA / cm 2 , deposition time 20min, thickness 4μm.
[0069] 5. Depositing a nano copper-silver alloy layer: using the method of step 3, depositing a nano copper-silver alloy layer on the micron-crystalline copper layer obtained in step 4.
[0070] 6. After the deposition is completed, a heterogeneous copper-silver alloy current collector with a hard layer to soft layer ratio of 2:1, a thickness ratio of 1:2, and a total thickness of 8 μm is obtained by peeling off from the nickel plate substrate. The heterogeneous copper-silver alloy current collector obtained by peeling is cleaned and dried.
[0071] Example 5
[0072] A method for preparing a heterogeneous copper alloy current collector comprises the following steps:
[0073] 1. Prepare nano copper-silver alloy electroplating solution: solution A is obtained by mixing 150 g / L potassium iodide, 10 g / L potassium nitrate and 40 mL / L silver nitrate at 0.1 M. 500 g / L copper sulfate and 150 g / L potassium pyrophosphate are dissolved in deionized water at a constant temperature to obtain solution B. Solution A and solution B are mixed in equal proportions, and then 0.005 g / L thiourea is added.
[0074] 2. Prepare micron-crystalline copper electroplating solution: the plating solution formula is: copper sulfate 75g / L, sulfuric acid 180g / L.
[0075] 3. Deposition of nano copper-silver alloy layer: In the nano copper-silver alloy electroplating solution, a nano copper-silver alloy layer is deposited on the nickel plate that has been ground, polished, cleaned, degreased and activated using direct current deposition. The deposition current density is 10 mA / cm 2 , deposition time 20min, thickness 2μm.
[0076] 4. Deposit a micron-crystalline copper layer: In a micron-crystalline copper electroplating solution, deposit a micron-crystalline copper layer on the nano-copper-silver alloy layer obtained in step 3 at a current density of 20 mA / cm 2 , deposition time 10min, thickness 2μm.
[0077] 5. Depositing a nano copper-silver alloy layer: using the method of step 3, depositing a nano copper-silver alloy layer on the micron-crystalline copper layer obtained in step 4.
[0078] 6. Depositing a micron-crystalline copper layer: using the method of step 4, depositing a micron-crystalline copper layer on the nano-copper-silver alloy layer obtained in step 5.
[0079] 7. Depositing a nano copper-silver alloy layer: using the method of step 3, depositing a nano copper-silver alloy layer on the micron-crystalline copper layer obtained in step 6.
[0080] 8. After the deposition is completed, a heterogeneous copper-silver alloy current collector with a hard layer to soft layer ratio of 3:2, a thickness ratio of 1:1, and a total thickness of 10 μm is obtained by peeling off from the nickel plate substrate, and the heterogeneous copper-silver alloy current collector obtained by peeling is cleaned and dried.
[0081] Example 6
[0082] A method for preparing a heterogeneous copper alloy current collector comprises the following steps:
[0083] 1. Prepare nano copper-tin alloy electroplating solution: 150g / L potassium pyrophosphate, 150g / L copper pyrophosphate, 30g / L stannous pyrophosphate, 10g / L sodium citrate, 40g / L dipotassium hydrogen phosphate, 30g / L nitrilotriacetic acid, then add 0.02g / L sodium polydisulfide dipropane sulfonate and 0.01g / L thiourea.
[0084] 2. Prepare micron-crystalline copper electroplating solution: the plating solution formula is: copper sulfate 75g / L, sulfuric acid 180g / L.
[0085] 3. Deposition of nano copper-tin alloy layer: In the nano copper-tin alloy electroplating solution, a nano copper-tin alloy layer is deposited on the nickel plate that has been ground, polished, cleaned, degreased and activated using direct current deposition. The deposition current density is 5 mA / cm 2 , deposition time 40min, thickness 2μm.
[0086] 4. Deposit a micron-crystalline copper layer: In a micron-crystalline copper electroplating solution, deposit a micron-crystalline copper layer on the nano-copper-tin alloy layer obtained in step 3 at a current density of 20 mA / cm 2 , deposition time 10min, thickness 2μm.
[0087] 5. Depositing a nano copper-tin alloy layer: using the method of step 3, depositing a nano copper-tin alloy layer on the micron-crystalline copper layer obtained in step 4.
[0088] 6. After the deposition is completed, a heterogeneous copper-tin alloy current collector with a hard layer and a soft layer ratio of 2:1, a thickness ratio of 1:1, and a total thickness of 6 μm is obtained by peeling off from the nickel plate substrate. The heterogeneous copper-tin alloy current collector obtained by peeling is cleaned and dried.
[0089] Comparative Example 1
[0090] A method for preparing a copper alloy current collector comprises the following steps:
[0091] 1. Weigh 50 g / L copper sulfate and 150 g / L potassium pyrophosphate and dissolve them in deionized water at a constant temperature to obtain solution A. Weigh 150 g / L potassium iodide, 10 g / L potassium nitrate, and 20 mL / L 0.1 M silver nitrate and dissolve them in deionized water at a constant temperature to obtain solution B. Mix solution A obtained in step 1 and solution B obtained in step 2 in equal proportions to obtain solution C. Weigh 0.005 g / L thiourea and dissolve it in solution C obtained in step 3 to obtain solution D.
[0092] 2. Place the polished, washed, and dried anode copper plate and cathode nickel plate in the D solution obtained in step 1 and deposit using a DC power supply at a current density of 10 mA / cm 2 , deposition time 120min, constant temperature 50℃, stirring speed 200rpm, thickness 12μm. The nanocrystalline copper-silver alloy current collector was peeled off from the substrate.
[0093] Comparative Example 2
[0094] A method for preparing a copper current collector comprises the following steps:
[0095] 1. Weigh 75 g / L copper sulfate and 180 g / L concentrated sulfuric acid and dissolve them in deionized water at room temperature to obtain a micron-crystalline copper electroplating solution.
[0096] 2. Place the polished, washed, and dried anode copper plate and cathode stainless steel plate in the nanocrystalline copper electroplating solution obtained in step 1, and use a DC power supply for deposition at a current density of 20 mA / cm 2 , deposition time 60min, constant temperature 25℃, stirring speed 500rpm, thickness 12μm.
[0097] 3. After the deposition is completed, the micron-crystalline copper foil current collector is peeled off from the nickel plate substrate, and the peeled micron-crystalline copper foil current collector is cleaned and dried.
[0098] The tensile strength, elongation, conductivity and peel strength of the current collectors obtained in the examples and comparative examples were tested, and the specific testing methods are as follows:
[0099] (1) Tensile strength and elongation
[0100] The test is carried out according to the standard GB / T 228-2002.
[0101] (2) Conductivity
[0102] The resistance value was measured using a constant current source and a multimeter, and the conductivity was calculated based on the length and cross-sectional area.
[0103] (3) Peel strength
[0104] The heterogeneous copper alloy current collector obtained in the embodiment is prepared into a long strip sample with a length of 200±0.5mm and a width of 15±0.25mm, and then the peel strength thereof is tested using a tensile testing machine, the chuck distance of the testing machine is 100±0.1mm, the tensile speed is 10mm / min, the test results are recorded, and the average value is taken as the peel strength of the corresponding embodiment.
[0105] The test results are shown in Table 1.
[0106] Table 1 Tensile strength, elongation, conductivity and peel strength of the materials obtained in the examples and comparative examples
[0107]
[0108] The bonding force between the polymer layer and the metal layer of the current collector whose middle soft layer is a polymer material is low. For example, in patent CN115763829 A, the bonding force is between 100-110N / m, and in patent CN 116207270 A, the peel strength is between 229-240N / m, while the peel strength of the heterogeneous copper alloy current collector obtained in the embodiment of the present invention is above 420N / m. It can be seen that the heterogeneous copper alloy current collector obtained by the embodiment of the present invention has excellent peel strength, indicating that it has excellent interlayer bonding force, and at the same time, it has better strength, ductility and good electrical conductivity, indicating that this heterogeneous structure can effectively improve the overall strength and plasticity of the current collector, and the preparation method adopts the traditional electroplating process, the process is simpler, and it is conducive to large-scale production.
[0109] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A heterogeneous copper alloy current collector, characterized in that: The invention comprises a nano copper alloy layer and a micron crystalline copper layer, wherein the micron crystalline copper layer is arranged between adjacent nano copper alloy layers.
2. The heterogeneous copper alloy current collector according to claim 1, characterized in that: The number of the micron-crystalline copper layer is 1-4.
3. The heterogeneous copper alloy current collector according to claim 1, characterized in that: The copper alloy includes one of a copper-silver alloy, a copper-tin alloy, a copper-nickel alloy and a copper-gold alloy; Preferably, the content of impurity elements in the copper alloy is less than or equal to 10%.
4. The heterogeneous copper alloy current collector according to claim 1, characterized in that: The thickness of the heterogeneous copper alloy current collector is 6-16 μm, and the thickness ratio of the nano copper alloy layer to the micron crystalline copper layer is (1-3):(1-3).
5. A method for preparing a heterogeneous copper alloy current collector according to any one of claims 1 to 4, characterized in that: The steps include: Copper alloy electroplating solution and micron-crystal copper electroplating solution are respectively prepared; In the plating solution, a nano copper alloy layer and a micron crystalline copper layer are electrodeposited on a substrate according to a set structure; The heterogeneous copper alloy current collector is obtained by peeling, washing and drying.
6. The preparation method according to claim 5, characterized in that: The copper alloy electroplating solution contains a refiner, which includes one or more of gelatin, thiourea, 2-mercaptobenzimidazole and sodium polydisulfide dipropane sulfonate; Preferably, the concentration of the refiner in the copper alloy electroplating solution is 0.005-0.05 g / L; Preferably, the micron-crystalline copper electroplating solution is one of a sulfate system, a nitrate system, a pyrophosphate system and a citrate system.
7. The preparation method according to claim 5, characterized in that: The electrodeposition includes one of direct current electrodeposition and pulse electrodeposition; Preferably, when the nano copper alloy layer is electrodeposited, the current density is 2-20 mA / cm 2 , the deposition time is 10-60min; Preferably, when the micron-crystalline copper layer is electrodeposited, the current density is 20-50 mA / cm 2 , the deposition time is 5-30min; Preferably, the electrodeposition process is carried out in a protective gas atmosphere. Preferably, the protective gas includes one of nitrogen, argon and helium.
8. The preparation method according to claim 5, characterized in that: After the nano copper alloy layer or micron crystalline copper layer is formed by the electrodeposition, it is washed with water, acid washed and washed with water before the next deposition.
9. A negative electrode sheet, characterized in that: The negative electrode sheet comprises a heterogeneous copper alloy current collector as described in any one of claims 1 to 4 or a heterogeneous copper alloy current collector prepared by the preparation method as described in any one of claims 5 to 8, and a mixed slurry layer containing a negative electrode material disposed on the surface of the heterogeneous copper alloy current collector.
10. A lithium ion battery, characterized in that: It comprises the heterogeneous copper alloy current collector described in any one of claims 1-4, the heterogeneous copper alloy current collector prepared by the preparation method described in any one of claims 5-8, or the negative electrode sheet described in claim 9.
Citation Information
Patent Citations
Air-stable long-acting reference electrode suitable for lithium battery
CN111969172A
Graded porous negative electrode current collector with lithium affinity and preparation method of graded porous negative electrode current collector
CN116914150A
Nanocrystalline copper-silver alloy current collector and preparation method thereof
CN118943381A
Nanometer crystal-micro crystal layered composite material and its preparation method
CN1757784A
Electrode collector, its manufacturing method, electrode for battery, its manufacturing method, and secondary battery
JP2008004462A